2011
DOI: 10.1002/erv.1158
|View full text |Cite
|
Sign up to set email alerts
|

The Scars of the Inner Critic: Perfectionism and Nonsuicidal Self‐Injury in Eating Disorders

Abstract: Nonsuicidal self-injury (NSSI) is quite common in eating disorder (ED) patients and we wondered whether this combined self-harming behaviour is related to perfectionism, a feature often found in ED patients. In addition, we examined associations between perfectionism and functions underlying NSSI and the possible mediating role of intrapersonal perfectionism in the association between perceived parental criticism and NSSI. In a sample of 95 ED patients, 38.9% reported at least one type of NSSI, and this subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 34 publications
(96 reference statements)
10
84
0
Order By: Relevance
“…We already know from cross sectional studies, that people who engage in NSSI are more highly self-critical than people who do not engage in NSSI (Hooley et al, 2010;St. Germain & Hooley, 2012;Claes et al, 2011;Gilbert et al, 2010). However, it is quite possible that high levels of self-criticism are a consequence of NSSI rather than an antecedent of NSSI and this warrants consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We already know from cross sectional studies, that people who engage in NSSI are more highly self-critical than people who do not engage in NSSI (Hooley et al, 2010;St. Germain & Hooley, 2012;Claes et al, 2011;Gilbert et al, 2010). However, it is quite possible that high levels of self-criticism are a consequence of NSSI rather than an antecedent of NSSI and this warrants consideration.…”
Section: Discussionmentioning
confidence: 99%
“…In a related program of research, Gilbert has also noted that self-harming behaviors are associated with self-criticism and negative feelings about the self . A form of self-criticism (evaluative concerns perfectionism) has also been linked to NSSI in a sample of inpatients with eating disorders (Claes, Soens, Vansteenkiste & Vandereycken, 2011). Moreover, using ecological momentary assessments, Nock, Prinstein and Sterba (2009) have reported that, in adolescents, the odds of engaging in NSSI were significantly increased in the presence of feelings of selfhatred and anger toward the self.…”
mentioning
confidence: 99%
“…Also, obsessive-compulsive and perfectionistic characteristics have been noted in both NSSI (Claes, Soenens, Vansteenkiste & Vandereycken, 2012;Hoff & Muehlenkamp, 2009) and ED samples (Boone, Soenens, Braet & Goossens, 2010;Serpell, Livingstone, Neiderman & Lask, 2002). Obsessive-compulsive characteristics may be demonstrated among individuals with more chronic and repetitive NSSI due to the reinforcing effects of the behavior, and individual's report that urges to self-injure can come on suddenly and be hard to resist (Washburn, Juzwin, Styer & Aldridge, 2010).…”
Section: Distal Factorsmentioning
confidence: 94%
“…Individuals with such introjects are harsher in their self-judgments than in their judgments of others, and these self-judgments often form the precursors to depressive episodes (Beck, 1983). Their harsh self-judgments may even manifest outwardly, through engagement in nonsuicidal self-injurious behaviors, which reflect the scars of the inner critic (Claes, Soenens, Vansteenkiste, & Vandereycken, 2012). Accordingly it is hardly surprising that adolescent depression and low self-esteem are associated with low autonomy (e.g., Noom, Dekovic, & Meeus, 1999).…”
Section: Introjection and Self-disparagement: Self-critical Depressionmentioning
confidence: 99%